Ion Binding to Quadruplex DNA Stems. Comparison of MM and QM Descriptions Reveals Sizable Polarization Effects Not Included in Contemporary Simulations - Gkionis, Konstantinos; Kruse, Holger; Platts, James A; Mládek, Arnošt; Koča, Jaroslav; Šponer, Jiří (Journal of chemical theory and computation, 2014)
Molecular mechanical (MM) force fields are commonly employed for biomolecular simulations. Despite their success, the nonpolarizable nature of contemporary additive force fields limits their performance, especially in long simulations and when strong polarization effects are present. Guanine quadruplex D(R)NA molecules have been successfully studied by MM simulations in the past. However, the G-stems are stabilized by a chain of monovalent cations that create sizable polarization effects. Indeed, simulation studies revealed several problems that have been tentatively attributed to the lack of polarization. Here, we provide a detailed comparison between quantum chemical (QM) DFT-D3 and MM potential energy surfaces of ion binding to G-stems and assess differences that may affect MM simulations. We suggest that MM describes binding of a single ion to the G-stem rather well. However, polarization effects become very significant when a second ion is present. We suggest that the MM approximation substantially limits accuracy of description of energy and dynamics of multiple ions inside the G-stems and binding of ions at the stem-loop junctions. The difference between QM and MM descriptions is also explored using symmetry-adapted perturbation theory and quantum theory of atoms in molecules analyses, which reveal a delicate balance of electrostatic and induction effects.